(untitled) (MAUSAM, 1962)
It is observed that short period group microseisms of period very close to one second occur in records of the short period vertical component Benioff Seismograph at Shillong on some occasions. It was observed by Walsh (1956) that great majority of the short period microseisms of period very near to 0.3 second are associated either with the approach or passage at the station of cold frontal type discontinuity or both or with local non frontal convective activity. The occurrence of microseism-storms under study indicates that these are not associated with each and every convective activity at the station. It is, however, believed that they are associated, with the passage of cold fronts in association with the secondaries of the western disturbances which move from west to east during the premonsoon months. The probable mechanism of generation of these microseisms is discussed.